Subpopulation targeting of pyruvate dehydrogenase and GLUT1 decouples metabolic heterogeneity during collective cancer cell invasion - R. Commander (Nature Portfolio, 2020)
The presence of phenotypic heterogeneity in collectively invading cells suggests cooperation amongst distinct subtypes of cells to promote invasion and metastasis. Here, the authors use chemical biology tools and report metabolic heterogeneity within the lung cancer collective invasion pack.